Beyond language crossing: exploring multilingualism and multicultural identities through popular music lyrics. Issue 4 (2nd October 2019) - Banda, Felix
ABSTRACT: Popular songs are loaded with critical social, cultural and historical information and provide blueprints for future semiotic practices. I draw on notions of language as social practice and poststructuralist performative identities to show how language practices in popular music intersect with multicultural practices and meaning making in fluid African multilingual contexts. I illustrate how multilingual and multicultural practices bring into dialogue the traditional and the modern, the rural and the urban, and the interconnectedness in the translocal and transnational cultural worlds. I unravel the layered and multidimensional configurations of new forms of ethnicity and fluid social identities and related multiple affiliations. Beyond the dualisms and time-space-age fixed language practices projected in many studies on urban youth languages in Africa, I maintain that these languages are connected to adult and rural languages. Otherwise, studies on urban youth languages risk being uprooted from local socio-cultural systems of meaning making, hence being a-cultural and a-historical. I conclude that the rural languages and traditional music styles are not just reflected in urban languages and modern music styles; they provide the framework on which new ways of languaging and music styles find connections with the transnational/global world of music.